Fault instability induced by ice melting in fractured rock - Sia, Wennie Su Siam (Nanyang Technological University, 2021)
This study aims to investigate the mechanism of slip failure on a melting fracture filled with quartz layer in granite when rising in temperature. The triaxial shear test is conducted using the MTS Test System with a low temperature controller to simulate ice melting in cold regions due to climate change. The results show the temperature rise can reduce the friction angle and the coefficient of internal friction which is based on the Mohr Coulomb failure criterion. Meanwhile, this explains that no change in shear stress would let the shear displacement going up when the temperature rises as it boosts the melting rate. Concurrently, the shear strength declines due to a reduction in the coefficient of friction. In this manner, climate change can affect the slope stability because of ice melting in rock fractures in cold regions. A deeper sense of the failure mechanism and slip characteristics of the fracture aids in the alleviation of climate change impact.